Addition of iron oxides in sediments enhances 2, 3, 4, 5-tetrachlorobiphenyl (PCB 61) dechlorination by low-voltage electric fields. Issue 42 (16th May 2017) - Liu, Xiaoping; Wan, Hui; Xue, Yuzhou; Feng, Chunhua; Wei, Chaohai
Abstract : The presence of iron oxides in sediments significantly improves anaerobic dechlorination of PCB ( i.e., PCB 61) in bioelectrochemical reactors. Abstract : Despite the growing interest in exploiting low-voltage electric fields for bioremediation of chlorinated contaminants, little information is known about whether iron-rich minerals, naturally abundant components in environments, affect bioelectrochemical dechlorination. Here, we made the first attempt to investigate the role of iron oxides on the dechlorination of polychlorinated biphenyls in a sediment-based bioelectrochemical reactor (BER) poised with a potential of −0.50 V vs. SCE (saturated calomel electrode). We found that the addition of iron oxides significantly enhanced the rate and extent of 2, 3, 4, 5-tetrachlorobiphenyl (PCB 61) transformation. Analysis of the bacterial structures suggested that the key species detected in the BERs were genera Geobacter and Desulfovibrio, well-known dissimilatory iron-reducing bacteria (DIRB) that were more dominant when iron oxides ( e.g., α-Fe2 O3 ) were added. A positive correlation between the rate constant of PCB 61 reduction and the biogenic adsorbed Fe(ii ) concentration suggests that DIRB-induced Fe(ii ) should be critical for enhancing PCB dechlorination in the system.